(untitled) (REMUNOM, 2025)
Synthetic polymers offer several industrial applications, however their persistence in the environment denotes a challenge. This work assessed the use of an acrylic-styrene copolymer (ASC) as the sole of carbon by Pseudomonas aeruginosa TGC04 and the ecotoxicological effects of the metabolites on germination and development of Cucumis anguria L. (Gherkin). The experiment was carried out in flasks containing minimal mineral medium added with ASC 1% and incubated for 72h at 30ºC. The contaminant reduction was 5,01%, determined by gravimetry. Compared to the control, it resulted in a partial recovery of plant development and demonstrated a significant difference in root biomass (p=0.041) and a tendency to significance in the aerial part biomass (p=0.065), i.e., stem and leaves. In conclusion, P. aeruginosa TGC04 showed potential for use in bioremediation.